Principles of corporate finance - Brealey, Richard A. (McGraw-Hill, 2003)
This book describes the theory and practice of corporate finance. It shows how to use financial theory to solve practical problems, and also to illuminate the facts and instititional material. Each chapter of the book closes with a summary, an annotated list of suggestions for further reading, a quick and easy quiz,and some more challenging questions and problems. Answers to the quiz questins may be found at the end of the books, along with present value and option tables and a glossary.